Kajian Komunikasi Multikultural dalam Pendidikan - Mutria Farhaeni (Jayapangus Press, 2020)
In this paper author researcher the study of multicultural communication in education. The used method is qualitative approach which based on literature materials that to examine multicultural communication in education. From the results of this for study auther narrated in descriptive form. It can be concluded that the changing dynamics of education are clearly seen in the vision and mission, the educational objectives in Indonesia until now where have not been fully achieved thus need to be refined. The educational systems are culturally different, but as becomes cultural changes so, education changes to and vice versa the educational system will always be oriented towards cultural change. Education is the process that makes a person enter to culture and make the behaviors which their follow culture. As a complex process, of course the system that can be supported the achievement of the goals of education itself is needed. Development and competence of multicultural teachers. Teachers should understand the cultural differences that exist in students to then make it a professional educator and competent in multicultural development.